Differential expression of platelet CD147 in moderate altitude conditions: implications for coronary plaque stability assessment - Chen, Yu; Lu, Si; Bao, Chun-Ping; Ren, Yong; Lv, Juan; Wang, Si-Jie; Wang, Li-Sha; Zi, Rui-Xi; Zhang, Xin; Yang, Li-Xia; Wang, Yan; Shi, Yan-Kun (Frontiers in Cardiovascular Medicine, 2025)
BackgroundAs a major contributor to global death rates, coronary heart disease (CHD) remains critical. This investigation examines CD147's utility for assessing plaque characteristics among CHD patients, with a focus on moderate altitude populations.MethodsInitially, high-throughput sequencing was performed on platelet samples obtained from three individuals with stable angina (SA) and three with unstable angina (UA), serving as the discovery cohort for subsequent bioinformatics analysis. Based on the insights gained from this initial phase, the investigation was extended to a larger cohort comprising 90 SA patients and 90 individuals diagnosed with acute coronary syndrome (ACS). Platelets isolated from these patients underwent flow cytometry analysis for CD147 expression. Furthermore, a logistic regression analysis incorporating traditional CHD risk factors was conducted to determine the odds ratio (OR) for CD147 expression in differentiating between stable and unstable plaques.ResultsHigh-throughput sequencing revealed distinct CD147 levels between SA and UA groups (log₂FC = 2.3). The logistic regression analysis demonstrated that heightened platelet CD147 correlated with plaque instability (OR = 9.21, 95% CI: 2.33–36.42, P = 0.002), persisting beyond conventional risk adjustment.ConclusionThis study identifies platelet CD147 as a promising predictor for differentiating plaque stability in CHD under moderate altitude conditions. Our findings suggest that CD147 not only contributes to platelet activation and thrombus formation but may also directly influence plaque stability. The impact of chronic hypoxia and other environmental stressors in moderate altitude regions on CD147 expression provides new insights for risk stratification and targeted therapeutic strategies in altitude-specific populations.